SHARIA-COMPLIANT CIVIL ENGINEERING: A STUDY ON THE DESIGN OF GENDER-SEPARATE FACILITIES IN PUBLIC TRANSPORTATION HUBS - Amelia Hayati; Dian Popi Oktari; Mukhtar Lutfie (Yayasan Adra Karima Hubbi, 2025)
The growing demand for infrastructure that aligns with Islamic ethical and social values has encouraged the integration of Sharia-compliant principles into modern civil engineering practices. Public transportation hubs, as shared urban spaces, present unique challenges in maintaining both efficiency and modesty, particularly regarding gender interaction. This study aims to examine the design and implementation of gender-separate facilities in public transportation hubs through a Sharia-compliant civil engineering perspective. The research employs a mixed-methods approach, combining qualitative content analysis of Islamic legal sources (fiqh al-‘imarah and maqasid al-shariah) with quantitative evaluation of design efficiency and user satisfaction from three case studies: Jakarta MRT, Kuala Lumpur Sentral, and Doha Metro. The findings reveal that gender-segregated layouts, when integrated with universal design principles, enhance both comfort and privacy without reducing operational capacity. The study also identifies key design variables—such as spatial zoning, circulation flow, and signage systems—that ensure compliance while maintaining inclusivity. The results emphasize that ethical urban design grounded in Sharia principles can coexist with modern engineering standards, promoting cultural sensitivity, sustainability, and social harmony.